Identification of Binding Mode of a Platinum (II) Complex, PtCl𝟐(DIP), and Calf Thymus DNA - Nahid Shahabadi; Soheila Kashanian; Azadeh Fatahi (Bioinorganic Chemistry and Applications)
The Pt(II) complex, PtCl2(DIP) (DIP = chelating dinitrogen ligand: 4,7-diphenyl-1,10-phenanthroline), was synthesized and characterized by elemental analysis (CHN) and 1H NMR and UV-vis techniques. The binding of this complex to calf thymus DNA was investigated using various physicochemical methods such as spectrophotometric, circular dichroism, spectrofluorometric, melting temperature, and viscosimetric techniques. Upon addition of the complex, important changes were observed in the characteristic UV-Vis bands (hyperchromism) of calf thymus DNA (CT-DNA): increase in melting temperature, sharp increase in specific viscosity of DNA, and induced CD spectral changes. Also the fluorescence spectral characteristics and interaction of Pt complex with DNA have been studied. Pt bound to DNA showed a marked decrease in the fluorescence intensity. The results show that both the complex and the NR molecules can intercalate competitively into the DNA double-helix structure. The experimental results show that the mode of binding of the this complex to DNA is classical intercalation.